Conventional vs. Sutureless Aortic Valve Bioprosthesis: Is Faster Better? - Ali Aljalloud; Ajay Moza; Jessica Paola Arias; Matthias Menne; Michael Becker; Konstantina Spetsotaki (Journal of Cardiovascular Development and Disease, 2023)
Purpose: The benefits of sutureless compared to conventional aortic valve prosthesis replacement remain controversial. Supposed advantages of sutureless aortic valve replacement include shortened cross-clamp and implantation time, as well as improved overall safety and good post-operative performance. We aimed to compare the early outcomes and performance of sutureless aortic valve replacement (su-AVR) with the sutureless Perceval (Corcym, Milan, Italy) vs. the conventional AVR with a conventional counterpart, in this case, the Labcor Dokimos Plus (LDP) aortic bioprosthesis. Methods: We compared two types of aortic valve prostheses, the sutureless (Corcym, Milan, Italy) and the conventional valve Labcor Dokimos Plus (LDP), implanted between August 2014 and May 2019 in our Department of Cardiac Surgery at RWTH Aachen University Hospital. Data were collected from 141 patients who received the Perceval (Corcym, Milan, Italy) and 138 who received the Labcor Dokimos Plus (LDP) aortic bioprosthesis. After matching the two groups considering STS mortality risk and pre-operative LDH levels, 201 patients were included in our final study cohort. Seventy-one patients (17 from the Perceval group and 54 from the Dokimos group) were excluded due to the lack of complete data, particularly standardized echocardiographic data (n = 71). Primary endpoints were 30-day mortality, length of hospital stay, and pacemaker implantation. Secondary endpoints were echocardiographic parameters, major adverse cardiovascular events, and prosthesis failure (grade II aortic regurgitation, paravalvular leak with reintervention). Results: Bypass and cross-clamp time proved to be shorter in the Perceval group, while hospital stays were longer. The faster implantation had no effect on the 30-day mortality primary endpoint. Transvalvular gradients were significantly higher in the Perceval group, in addition to a smaller effective orifice area. The LDH values were remarkably higher post-operatively in the Perceval group. Conclusions: Regarding the clinical outcomes, Perceval was equivalent and not superior to the Dokimus bioprosthesis. The suitability of a Perceval prosthesis implantation must be determined on a case-by-case basis and reserved for elderly patients with increased comorbidity.